Comparative studies and risk analysis of heavy metal contaminants in Solanum tuberosum (Irish Potato) and Daucus carota (Carrot) in Bokkos LGA of Plateau State, Nigeria - Nangbes, Jacob Gungsat; Lawam, Tobias Deban; Wufem, Buba Mamman; Dawam, Nancy Naanogot (International Journal Labs, 2024)
The study aims to compare and analyze the levels of heavy metal contaminants in Solanum tuberosum (Irish Potato) and Daucus carota (Carrot) in Bokkos Local Government Area Plateau State, Nigeria, assessing potential health risks associated with consuming these crops. The research was focused to five heavy metals (Cd, Cr, Cu, Ni, and Pb) in Irish potato and carrot sample from five different farms. The concentrations of these metals were gotten in decreasing order as follows: (DIM) Irish potato (A) Cd > Pb > Cr > Ni; (EDI) Irish potatoes (C) Cu > P B > Cr B > Ni B > Cd; (DI) carrot (A), Cu > B > Cu B > P Ni; and (DIMA) carrot(A) Pb Cd Cu Pb. The health risk assessment indices for the populations through the consumption of contaminated fish were estimated based on the daily intake of metals relative to the reference oral dose (RfD) for each metal. The mean concentration of Pb, Cd, Ni and Cd in tubers was less than the recommended values of FAO/WHO. The risk analysis factors considered were transfer factor (TF), EDI, DIM, bioaccumulation factor (BF), target hazard quotient (THQ), and Health risk index (HRI) evaluated for this study showed moderate to less high risk levels with respect to human exposure through consumption of the vegetables and not the soil as may be indicate in transfer factor. It is therefore recommended to monitor periodically the agricultural farmlands using a different analysis techniques with a view for possible remediation.